Validação de um novo sistema de manometria esofágica de alta resolução por perfusão de água - Silva, Rogerio Mariotto Bitetti Da [UNIFESP] (2019)
Introduction: High resolution esophageal manometry (MEAR) has brought benefits over conventional manometry. This study aims to determine and validate normal values in a new water perfusion HRM system. Material and Method: Normal values were defined from the study of 32 healthy volunteers (group 1). The values were validated by a study of 225 individuals who underwent HRM for clinical complaints, subdivided into: gastroesophageal reflux disease (GERD) (group 2), achalasia (group 3), systemic diseases (group 4) and dysphagia (group 5). The system used was water perfusion with 24 sensors (Multiplex, Alacer Biomedica, São Paulo, Brazil). For the upper esophageal sphincter (UES), the parameters studied were basal and relaxation pressures. The parameters of the esophageal body were: distal contractility integral (DCI), distal latency (DL) and break. The parameters of the lower esophageal sphincter (LES) were basal and relaxation pressures and integrated relaxation pressure (IRP). Results: Normal values were: upper esophageal sphincter (UES) basal pressure 16.7-184.37 (mmHg), DL: 6.2-9.1 (s), DCI: 82.72-3836.61 (mmHg .s.cm), break: <7.19 (cm), LES basal pressure: 4.89-37.16 (mmHg), IRP: 0.55-15.45 (mmHg). In group 2, a hypotonic LES was found in 49% of individuals with confirmed GERD and 28% in pH-negative GERD. In group 3, aperistalse was found in all individuals. In the group 4 aperistalsis was observed in all cases. And in group 5 only 1 (14%) had normal HRM. Conclusions: We determine the normality values. Normal values are discriminating against changes in esophageal motility, therefore clinically validated.